Identifying priority areas and spatial fisheries impact for addressing shark conservation in a data-limited context (2017)
Shark distribution and fishing grounds used by local communities are usually overlapped, although this coincidence is not straightforwardly distinguished in a data-limited context. We aim to delimit critical areas for shark conservation using a comprehensive spatial model to determine the co-occurrence area of the most fished shark species considering the distribution of the fishing effort and protection effectiveness of MPA'S in the Colombian Caribbean. Predicted distribution areas for nine frequent landed species were obtained using a maximum entropy (MaxEnt) species distribution model fed with species presence and environmental open-access data, while the fishing effort was derived from interview-based maps already available. The co-occurrence areas (COAs) were derived from the nine shark species habitat suitability models by using a 70% and 85% threshold cut, for defining a general and highest probability areas of distribution, respectively. Three independent co-occurrence areas were delimited along the Colombian Caribbean Sea: Morrosquillo Gulf, Santa Marta-Guajira and San Andres and Providence Archipelago, without finding an environmental link between them. By considering the highest probability of co-occurrence, 16 areas were well differentiated. Fishing grounds and COAs were unequally overlapped (total: 45%, mean: 26,76%) while marine protected areas did not offer effective protection against fishing pressure in areas identified as critical for conservation of the shark species in the analysis. This suggests a noticeable spatial relationship between co-occurrence shark areas and fishing grounds used by local fishing communities. The use of this methodology enables identification of co-occurrence areas in a data-limited context, which can be used as starting point for defining the priority areas for shark conservation in the Colombian Caribbean which will allow stakeholders to implement future management guidelines in well-defined areas.